2010
DOI: 10.7768/1948-5123.1033
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Community and Place in an Outdoor Orientation Program

Abstract: This study investigated outcomes of a college outdoor orientation program that utilized 3, 4, 5, and 12-day adventure based trips. Sense of community and sense of place were measured using a one-sample pre/post-test design (n = 118). Paired sample t-tests were implemented to explore differences and, in general, students reported significant changes following participation. Students demonstrated increases in the number of their friends, trusted individuals, and 6 of the 7 factorial components measuring sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
7
0
2
Order By: Relevance
“…The literature repeatedly encourages researchers to examine the various mechanisms and factors that produce and influence group experiences in outdoor experiential programs (Ewert & McAvoy, 2000;McAvoy, Mitten, Stringer, Steckart, & Sproles, 1996). One such factor is the development of sense of community during outdoor education curricula within a variety of contexts (Austin, Martin, Yoshino, Schanning, Ogle, & Mittelstaedt, 2010;Breunig, O'Connell, Todd, Anderson, & Young, 2010;Lyons, 2003). Sense of community has been characterized as the "feeling an individual has about belonging to a group and involves the strength of the attachment people feel for their communities or group" (Halamova, 2001, p. 137).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The literature repeatedly encourages researchers to examine the various mechanisms and factors that produce and influence group experiences in outdoor experiential programs (Ewert & McAvoy, 2000;McAvoy, Mitten, Stringer, Steckart, & Sproles, 1996). One such factor is the development of sense of community during outdoor education curricula within a variety of contexts (Austin, Martin, Yoshino, Schanning, Ogle, & Mittelstaedt, 2010;Breunig, O'Connell, Todd, Anderson, & Young, 2010;Lyons, 2003). Sense of community has been characterized as the "feeling an individual has about belonging to a group and involves the strength of the attachment people feel for their communities or group" (Halamova, 2001, p. 137).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Researchers have generally reported that strong interpersonal connections develop. For example, Wolfe and Kay (2011) noted that students in their study referred to their connections with others as “family.” Similarly, Austin et al (2010) reported that students indicated significant changes in three of four domains of community including personal comfort, cross-cultural relationships, and unfamiliar social environments. Students also indicated they had a significant increase in the number of friends and peers whom they trusted.…”
Section: Review Of Literaturementioning
confidence: 93%
“…With this in mind, many universities have turned to OOPs to provide students with positive transition experiences (Austin et al, 2010; Bell & Holmes, 2011; Hill, Nolan, & Scrogin, 2010; Wolfe & Kay, 2011). The creation and maintenance of social support networks is a primary objective and has been found to have both short-term and long-term positive effects (Gass et al, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…5 Outdoor orientation programs have also been shown to positively impact incoming students' sense of place and community. 6 Students in successful orientation programs have self-identified growth in the areas of social competence, achievement motivation, intellectual flexibility, task leadership, emotional control, active initiative, and self-confidence. 4 These positive changes were attributed to four factors of the programs: a wilderness setting, small group size, fellow participants, and peer leadership.…”
Section: Literature Reviewmentioning
confidence: 99%